Challenging Malaysia's status quo - Lim, Teck Ghee (Strategic Information and Research Development Centre, 2018)
History professor, consumer advocate, policy analyst and public intellectual par excellence Dr Lim Teck Ghee has put together this important collection of critical essays on the existential crisis of the Malaysian nation today. Through these essays, Dr Lim systematically exposes the poor state of governance in the Malaysian state and the flaws of its past and current policies. His pointed analyses of how and why we must change ineffectual and moribund policies is essential reading for academicians, politicians and activists. - Johan Saravanamuttu, Adjunct Senior Fellow, S. Rajaratnam School of International Studies (RSIS), Singapore. The life time spent by Dr Li Teck Ghee on studying and analyzing issues affecting the well-being of Malaysia and the world is exhibited an impressive fashion in this collection of articles. Often controversial, always informed, his incisive words confirm his standing as one of the country's most intrepid and resolute public intellectuals.